2005
DOI: 10.1093/brain/awh491
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticographic high gamma activity versus electrical cortical stimulation mapping of naming

Abstract: Subdural electrocorticographic (ECoG) recordings in patients undergoing epilepsy surgery have shown that functional activation is associated with event-related broadband gamma activity in a higher frequency range (>70 Hz) than previously studied in human scalp EEG. To investigate the utility of this high gamma activity (HGA) for mapping language cortex, we compared its neuroanatomical distribution with functional maps derived from electrical cortical stimulation (ECS), which remains the gold standard for predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
233
3
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 245 publications
(256 citation statements)
references
References 47 publications
17
233
3
3
Order By: Relevance
“…They have shown that broadband power increases, revealed at high frequencies, are typically local, on areas primarily involved in the task [Crone et al, 1998a;Miller et al, 2009b], and these high frequency changes correspond well to sites found with electrocortical stimulation of language and motor regions Sinai et al, 2005]. Power decreases in low frequency sensorimotor rhythms are distributed over larger areas of cortex [Crone et al, 1998b;Miller et al, 2007].…”
Section: Introductionsupporting
confidence: 53%
“…They have shown that broadband power increases, revealed at high frequencies, are typically local, on areas primarily involved in the task [Crone et al, 1998a;Miller et al, 2009b], and these high frequency changes correspond well to sites found with electrocortical stimulation of language and motor regions Sinai et al, 2005]. Power decreases in low frequency sensorimotor rhythms are distributed over larger areas of cortex [Crone et al, 1998b;Miller et al, 2007].…”
Section: Introductionsupporting
confidence: 53%
“…High c band activity and its dynamic time-dependent behavior have also been examined with subdural electrocorticographic (ECoG) recordings [20][21][22]. In our results with scalp EEGs, we do see some very focused high c band activity related to the language and baseline.…”
Section: Discussionmentioning
confidence: 59%
“…These human results have since been replicated and further extended for decoding of arm movements (Pistohl et al, 2008;Sanchez et al, 2008), flexion of individual fingers (Kubanek et al, 2007), and even specific aspects (such as the type of phoneme) of actual or imagined speech (Schalk et al, 2007a). Finally, several studies demonstrated that it is possible to combine general understanding of motor-related ECoG responses (Crone et al, 1998a,b;Aoki et al, 1999;Graimann et al, 2002;Sinai et al, 2005;Leuthardt et al, 2007;Miller et al, 2007) with the more specific understanding described above to implement different ECoG-based BCIs (Leuthardt et al, 2004;Wilson et al, 2006;Felton et al, 2007;Schalk et al, 2008) in humans using the BCI2000 software framework . These studies showed that ECoG supports accurate nonmuscular one-or two-dimensional movement control in humans with little subject training.…”
Section: Signal Fidelity Of Ecogmentioning
confidence: 99%